Regulation of Heme Synthesis by Mitochondrial Homeostasis Proteins - Yien, Yvette Y.; Perfetto, Mark (Frontiers in Cell and Developmental Biology, 2022)
Heme plays a central role in diverse, life-essential processes that range from ubiquitous, housekeeping pathways such as respiration, to highly cell-specific ones such as oxygen transport by hemoglobin. The regulation of heme synthesis and its utilization is highly regulated and cell-specific. In this review, we have attempted to understand how the heme synthesis machinery is regulated by mitochondrial homeostasis as a means of coupling heme synthesis to its utilization and to the metabolic requirements of the cell. We have focused on discussing the regulation of mitochondrial heme synthesis enzymes by housekeeping proteins, transport of heme intermediates, and regulation of heme synthesis by macromolecular complex formation and mitochondrial metabolism. Recently discovered mechanisms are discussed in the context of the model organisms in which they were identified, while more established work is discussed in light of technological advancements.